EFEKTIVITAS PENGGUNAAN SOFTWARE HADITS TERHADAP PRESTASI BELAJAR TAKHRIJ AL-HADITS - Rizky Lestari; Alimron Alimron; Ahmad Syarifuddin; Maryamah Maryamah; Nurlaila Nurlaila (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2023)
The use of hadith software as one of the learning media in the Takhrij Al-Hadith subject is not fully optimized. Related to the low achievement of students' learning in this lecture, among others; students become lazy and aren’t serious about making takhrij hadith with correct efforts and following the guidelines. This study is to obtain objective information about the different uses of the hadith software on the achievements learning of Takhrij Al-Hadith in PAI students of the Al-Qur’an Hadith concentration class of 2016 UIN Raden Fatah Palembang. The method used in this research is a quantitative method using descriptive analysis. From the research results obtained, the data were analyzed descriptively. Then, to learn more about using software, it has been analyzed with the Product Moment detection formula. This is used to determine the interaction between the two variables. Furthermore, the